2018
DOI: 10.1108/ara-05-2017-0080
|View full text |Cite
|
Sign up to set email alerts
|

Product market competition, state-ownership, corporate governance and firm performance

Abstract: Purpose The purpose of this paper is to examine the association between firm performance and product market competition (PMC), and then examine the mitigation effect of corporate governance and/or state-ownership (SOEs) in the association between PMC and firm performance using Chinese listed firms. Design/methodology/approach The authors consider three determinants of the PMC that affect the nature of competition, and use market concentration, product substitutability and market size as proxies for PMC. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
56
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(67 citation statements)
references
References 70 publications
6
56
0
5
Order By: Relevance
“…Shiet al (2018) revealed that marketing performance has an effect on financial performance. A study Liu et al (2018) showed that higher product market competition is associated with lower firm performance. This argument justifies the following fifth hypothesis:…”
Section: Marketing Performance and Financial Performancementioning
confidence: 99%
“…Shiet al (2018) revealed that marketing performance has an effect on financial performance. A study Liu et al (2018) showed that higher product market competition is associated with lower firm performance. This argument justifies the following fifth hypothesis:…”
Section: Marketing Performance and Financial Performancementioning
confidence: 99%
“…Adanya manajemen small and medium-sized enterprises (SME) dapat meningkatkan kinerja perusahaan dengan berinvestasi dalam pengembangan kemampuan product management (PM) eksternal dan internal (Roach, 2011). Namun, perusahaan mencapai kinerja yang lebih rendah ketika mereka dihadapkan dengan product market competition (PMC) yang lebih tinggi (Liu, Qu, & Hanam, 2018). Hal tersebut dikarenakan tata kelola perusahaan yang baik dapat memoderasi efek negatif PMC yang lebih tinggi pada kinerja perusahaan.…”
Section: Kinerja Perusahaanunclassified
“…Zahra (2008) memiliki pendapat bahwa firm performance dapat diukur dengan laba perusahaan atas aset (ROA) yang dikumpulkan selama tiga tahun dari pengumpulan data survei ROA di awal periode. Manajer akan bekerja kerja keras untuk meningkatkan produktivitas agar dapat mengurangi biaya dan pada akhirnya akan meningkatkan firm performance, (Liu, Qu, & Haman, 2018), menggunakan penelitian dengan laba atas aset (ROA) sebgai ukuran kinerja perusahaan berbasis akuntansi. Thoumrungroje & Tansuhaj (2005) membenarkan bahwa firm performance bergantung pada postur yang strategis dari perusahaannya (strategic posture), lingkungan, dan startegi yang dipilih.…”
Section: Firm Performanceunclassified